Cow Manure Disposal Using an Earthworm Bio-Bed and the Development of a Vermicompost-Based Substrate for Capsicum Seedlings. Issue 3 (3rd July 2018) - Haitao, Zhao; Tianpeng, Li; Yuhua, Shan; Ke, Feng; Zhijun, Yan; Qiande, Zhu
ABSTRACT: Vermicompost is becoming an important substitute for peat in horticulture due to the negative consequences of peat depletion. There is no aerobic fermentation pretreatment in the process of direct digestion of fresh cow manure by earthworms, which resulted in different properties of vermicompost compared with traditional treatment methods. However, there is limited knowledge on the properties of vermicompost in the direct earthworm digestion process. In the present study, a large-scale earthworm bio-bed was used to convert fresh cow manure into vermicompost, and then the physical, chemical, and microbial properties of the vermicompost were determined. To study the influence of mineral nutrient additions, vermicompost was mixed with vermiculite at a ratio of 4:1 (v/v), and was then used as the growth medium for capsicum seedlings. The results showed that nitrate nitrogen (243.39 mg/kg), ammonium nitrogen (50.38 mg/kg), total phosphorus (47.61 g/kg), available phosphorus (41.68 g/kg), catalase activity (2.17 mL/g·h), bacterial biomass (3.60 × 10 7 cfu/g), actinobacterial biomass (2.40 × 10 7 cfu/g), and fungal biomass (1.55 × 10 6 cfu/g) measurements were significantly higher in vermicompost than in the parent material. However, moisture (50.01%), electrical conductivity (2.07 mS/cm), total nitrogen (8.52 g/kg), organic matter (28.47%), and urease activity (0.63 mL/g·h) were significantly lower in the vermicompost compared to the parent material. The shoot and root morphological indices and the capsicum biomass accumulation measurements in the vermicompost treatments were superior to those found in the commercial peat medium (CK). Leaf expansion (14.83 cm), shoot height (24.20 cm), stem diameter (4.38 cm), leaf number (16.20 No.), root length (352.83 cm), root surface area (60.30 cm 2 ), root diameter (0.61 mm), and root volume (0.92cm 3 ) significantly higher in vermicompost-vermiculite mixed media with added urea (0.5 kg/m 3 ), superphosphate (10.0 kg/m 3 ), and potassium chloride (1.0 kg/m 3 ) than in CK at the late seedling growth stage. The addition of mineral nutrients (NPK) had little effect on the physical properties of the vermicompost media, but it improved the available nutrients. In summary, fresh cow manure without pre-treatment can be processed into vermicompost using a large-scale earthworm bio-bed. Vermicompost could serve as an alternative for commercial peat media in the cultivation of capsicum plug seedlings, and the beneficial effects of adding NPK gradually emerged as the seedling growth time increased.